Ecoficciones y procesos artísticos: la producción de obras artísticas y la relación simbólica con el territorio habitado y construido - Villavicencio Monti, Karla Paola (2024)
This article intends to explain the different possibilities of representation of what we will call “fictional ecosystems”, being imaginary ecosystems that are developed through visual representation, highlighting their importance to establish, develop and maintain a connection with the inhabited territory, as fundamental relationship to build a society that questions the subjectivities established in the coexistence with the natural, humanized and collective environment. Thus, an explanatory line is developed, which answers the following question, can elements of visual representation be used for the creation of “fictional ecosystems” that help to question the relationship that we build with our natural and humanized ecosystems in the contemporary environment and its corresponding problems? The answer is built through a methodology created using two phases of analysis. An explanatory line is drawn through artistic proposals made in Peru, developed on different supports and using various means, such as painting, drawing, installation and video art. The first phase called “Ritualized Territory and Creation” deals with the relationship between own experiences in the territory of the artists and their creative processes; the second phase “Territory and Cultural Imaginaries”, highlights the intrinsic link between the experiences established in the previous phase and the construction of imaginaries that enable to question our cultural and ethical environment. It is attempted to highlight the importance and the fundamental role of the abovementioned representations as a bridge for a better understanding of the framework of subjectivities that triggers the relationship between natural and humanized ecosystems. This methodology will be explained through the development of four projects: “Abglutia”. “Peligro de Extinción”, “Natural Sense Making” and finally, “Pestes”. Through the analysis of these projects, it is recognized that the visual representations of these fictional ecosystems are useful and necessary to develop a critical view that promotes introspection and questioning about the relationship with our natural environment and the ecosystems that have influence on it, enabling to establish in our collective relationships the development of a symbolic relationship with the territory that we inhabit and build.